POLA MAKAN DAN TINGKAT KECUKUPAN GIZI BALITA PADA KELUARGA PETANI JAGUNG - Veronica Lia Andriani; Yaktiworo Indriani; Rabiatul Adawiyah (Lampung University, 2015)
This study aims to determine the corn farm income, food pattern and the Nutritional adequacy level (NAL) of under five year’s old children (balita) from The Corn Farmers’ Families. The study usedsurvey method by involvingall 58 balita in Pematang Baru Village of Palas Subdistrict of South Lampung Regency. This research location was chosen for it has the largest corn producing areas. The data was analyzed descriptively and statistically by multiple linear regression quantitavely by calculating R/C ratio and NAL. The study results showed that corn farming was profitable for its total R/C value was greater than 1 and R/C of cash cost was1.49. Food Pattern of the balita indicated by the frequency of consumption per week of rice 16.17 times, packaging milk 2.36 times, spinach 1.30 times, banana 1.21 times, and tea 2,34 times. The average NAL of was as follows:energy 59.31%, protein 88.86%, fat 35.97, carbohydrate 73.14%, calcium 29.54%, phosphorus 58.54%, Fe 71.63 percent, vitamin A 69.93%, and vitamin C 52.61%. The NAL of energy, fat, calcium, phosphorus, vitamin A and vitamin C fell into the category of severe deficit since they’re less than 70 percent. Key words: balita, food pattern, NAL